-83n+3n=24

Simplify each term.

Combine n and 83.

-n⋅83+3n=24

Move 8 to the left of n.

-8n3+3n=24

-8n3+3n=24

To write 3n as a fraction with a common denominator, multiply by 33.

-8n3+3n⋅33=24

Simplify terms.

Combine 3n and 33.

-8n3+3n⋅33=24

Combine the numerators over the common denominator.

-8n+3n⋅33=24

-8n+3n⋅33=24

Simplify the numerator.

Factor n out of -8n+3n⋅3.

Factor n out of -8n.

n⋅-8+3n⋅33=24

Factor n out of 3n⋅3.

n⋅-8+n(3⋅3)3=24

Factor n out of n⋅-8+n(3⋅3).

n(-8+3⋅3)3=24

n(-8+3⋅3)3=24

Multiply 3 by 3.

n(-8+9)3=24

Add -8 and 9.

n⋅13=24

n⋅13=24

Multiply n by 1.

n3=24

n3=24

Multiply both sides of the equation by 3.

3⋅n3=3⋅24

Cancel the common factor of 3.

Cancel the common factor.

3⋅n3=3⋅24

Rewrite the expression.

n=3⋅24

n=3⋅24

Multiply 3 by 24.

n=72

n=72

Solve for n -8/3n+3n=24